"Digital Simulation of Osteotomy Reduction of a Prominent Zygomatic Arch". Issue 7 (October 2021) - Tao, Qiao; Min, Hou; Yangyang, Lin; Jinghao, Duan; Qiuyu, Cao
Abstract : Objective: To analyze the value of simulated surgery in predicting the outcome of individualized surgical reduction of a prominent zygomatic arch. Methods: Computed tomography data were obtained from the electronic records of 15 patients who underwent surgery at Tianjin Stomatological Hospital for prominent zygoma. The data were imported into Mimics 23.0. Left and right three-dimensional (3D) zygoma models were created through standard procedures. In the 3D models, a wedge-shaped cut of the zygomatic bone was pushed inward, and the osteotomy position of the zygomatic arch was taken as a variable to simulate the reduction malarplasty. The reduction effect was calculated from the simulated movement of the fracture end of the zygomatic arch from internal pushing forces. Stable versus high-efficiency internal pushing areas were defined based on the amount of movement. Mean values with 95% confidence intervals (CI) were calculated for the areas data. Results: The anterior edge of the stable internal pushing osteotomy area was located in front of the articular tubercle point (95% CI: 10.64–11.89 mm). The posterior edge of the stable internal pushing area was located in front of the articular tubercle point (95% CI: 7.8–9.13 mm). The posterior edge of the high-efficiency internal pushing area was located in front of the articular tubercle point (95% CI: 4.7–5.73 mm). Conclusion: Stable and high-efficiency internal pushing areas were detected above the zygomatic arch. The simulation showed that osteotomy in these areas can provide different degrees of zygomatic arch reduction. Abstract : Supplemental Digital Content is available in the text